PROGNOSTIC IMPACT OF CD34 EXPRESSION IN PAEDIATRIC PATIENTS WITH ACUTE LYMPHOBLASTIC LEUKAEMIA - Noor, Afshan; Manzar Bozdar,; Malik, Hamid Saeed; Riaz, Muhammad Omair; Mahmood, Rafia; Nighat Seema,; Irshad, Romana (Journal of Ayub Medical College Abbottabad, 2024)
Background: Acute lymphoblastic leukaemia (ALL) affects adults as well as children. Malignant transformation and proliferation occur in lymphoid progenitor cells found in bone marrow, blood, and extra-medullary locations. Precursor B-cell types account for the majority of ALL cases. Objective was to measure the expression of CD34 positive cells as a prognosis-related marker in paediatric Acute Lymphoblastic Leukaemia (ALL). It was a prospective cohort study, conducted at the Armed Forces Institute of Pathology, Rawalpindi, from July 2022 till July 2023. Methods: This study investigates the expression of CD34, a marker associated with hematopoietic stem and progenitor cells, in paediatric ALL and its correlation with clinical outcomes. Our study included 122 children aged 18 years or younger, newly diagnosed with ALL. Patients were diagnosed on complete blood counts and initial bone marrow examination, followed by flow cytometry. Essential molecular and cytogenetic studies were also carried out, followed by “day 29” induction marrow to assess the remission status of the patients under treatment protocols. CD34 expression was measured by flow cytometry and correlated with the clinic-haematological parameters of the patients for identification of risk groups. Results: The study comprised of 78 (63.9%) males and 44 (36.1%) females. Overall, 79% of patients showed CD34 expression while its expression was absent in 21% patients. CD34 expression was correlated with higher total leucocyte count, increased peripheral blood blast percentage, decreased platelet count and increased transfusion dependency. Minimal residual disease status was significantly better in CD34 negative patients as compared to CD34 positive patients. Conclusion: Expression of CD34 is an adverse prognostic marker in ALL patients and the presence of this antigen affects the clinical outcome of these patients.